Young women's experiences of intrusive behavior in 12 countries - Sheridan, Lorraine; Scott, A.; Roberts, K. (Wiley-Liss Inc., 2015)
© 2015 Wiley Periodicals, Inc. The present study provides international comparisons of young women's (N=1,734) self-reported experiences of intrusive activities enacted by men. Undergraduate psychology students from 12 countries (Armenia, Australia, England, Egypt, Finland, India, Indonesia, Italy, Japan, Portugal, Scotland, and Trinidad) indicated which of 47 intrusive activities they had personally experienced. Intrusive behavior was not uncommon overall, although large differences were apparent between countries when women's personal experiences of specific intrusive activities were compared. Correlations were carried out between self-reported intrusive experiences, the Gender Empowerment Measure (GEM), and Hofstede's dimensions of national cultures. The primary associations were between women's experiences of intrusive behavior and the level of power they are afforded within the 12 countries. Women from countries with higher GEM scores reported experiencing more intrusive activities relating to courtship and requests for sex, while the experiences of women from countries with lower GEM scores related more to monitoring and ownership. Intrusive activities, many of them constituent of harassment and stalking, would appear to be widespread and universal, and their incidence and particular form reflect national level gender inequalities.